Design universal e mobilidade urbana: a experiência do usuário como referência de qualidade do BRT Move de Belo Horizonte - Flavia Papini Horta (2017)
This work investigated the quality of the BRT Move system through the eyes of users who have problems of mobility, under the foundations of universal design. For that, a research strategy was developed in two stages. The first one built a theoretical conceptual base that covered topics such as the user and environment relationship, the meanings of autonomy and independence, the importance of accessibility and universal design, and the concept of urban mobility. For the application of the theories analyzed, a study case, the Hospital Odilon Behrens station, was established. Having defined these parameters and the place of study, the second stage of investigation has followed. For that, a questionnaire was developed that sought, through the theories of post occupation analysis, semantic differential, analogy by images and walkthrough method, to obtain the most information and opinions of the users regarding the BRT Move system. The questionnaire was applied to 17 people with mobility problems. Two other people participated in walktrough interviews. The results converge to a complex scenario of mobility problems presented in the case stud. Conclusions indicate that despite accessibility flaws to comply with the principles of universal design in the 'Move' BRT system, there are positive remarks mainly due to the existence of a new transportation system. Also, conversely, there are negative reports of users' experiences.